Agroecology in the Brazilian Amazon. A Review - Souza, Caio Cezar Ferreira de; Santos, Marcos Antônio Souza dos; Rebello, Fabrício Khoury; Martins, Cyntia Meireles; Lopes, Maria Lúcia Bahia; Barbosa, Antônia do Socorro Aleixo; Saraiva, Joyce dos Santos (Fronteira: Journal of Social, Technological and Environmental Science, 2021)
Agroecological practices are alternatives for valuing and conserving the biodiversity of the Amazon as well as for integrating family farmers who survive from the exploitation of natural resources in the face of the expansion of large agricultural projects that have advanced in the region. In this respect, the objective of this study was to evaluate the scientific production related to agroecology in the Brazilian Amazon, in order to identify the main research gaps and set the foundations for new studies that will strengthen the debate on and policies to encourage sustainable agriculture. Our methodology was based on a systematic review of the literature using four academic research databases. The studies were published from 2000 to 2019. Through our database research, we obtained 36 articles that focused on agroecology in the Brazilian Amazon. Our results showed a certain level of diversity in terms of the geographic distribution of the municipalities included in the studies analyzed. Additionally, we detected diversity in terms of the dimensions addressed. For instance, reference was made to sustainable production systems based on agroecological principles, with emphasis on agroforestry systems. Additionally, socioeconomic and cultural aspects, such as the valuation of traditional knowledge and the importance of women in rural areas, were analyzed. Thus, the realization of in-depth studies that will analyze the process of agroecological transition with the use of different techniques, such as the statistical treatment of data and geoprocessing, can qualify agricultural production based on the agroecological practices in the Amazon.